The Effect of Paternal Age on Fetal Birth Outcomes - Amina P. Alio PhD; Hamisu M. Salihu MD, PhD; Cheri McIntosh MPH; Euna M. August MPH; Hanna Weldeselasse MS; Emanny Sanchez BS; Alfred K. Mbah PhD (American Journal of Men's Health, 2012)
Research investigating the role of paternal age in adverse birth outcomes is limited. This population-based retrospective cohort study used the Missouri maternally linked data set from 1989 to 2005 to assess whether paternal age affects fetal birth outcomes: low birth weight (LBW), preterm birth (PTB), stillbirth, and small size for gestational age (SGA). We examined these outcomes among infants across seven paternal age-groups (<20, 20-24, 25-29, 30-34, 35-39, 40-45, and >45 years) using the generalized estimating equation framework. Compared with infants born to younger fathers (25-29 years), infants born to fathers aged 40 to 45 years had a 24% increased risk of stillbirth but a reduced risk of SGA. A 48% increased risk of late stillbirth was observed in infants born to advanced paternal age (>45 years). Moreover, advanced paternal age (>45 years) was observed to result in a 19%, 13%, and 29% greater risk for LBW, PTB, and VPTB (very preterm birth) infants, respectively. Infants born to fathers aged 30 to 39 years had a lower risk of LBW, PTB, and SGA, whereas those born to fathers aged 24 years or younger had an elevated likelihood of experiencing these same adverse outcomes. These findings demonstrate that paternal age influences birth outcomes and warrants further investigation.